Transforming Soft Law Into Binding Commitments in International Human Rights - Muh Habibulloh; Hawwin Muzakki; Habiburrohman; Yuli Umro'atin (International Journal of Law, 2025)
This article explores the evolving role of soft law in the international human rights framework and analyzes how it can be transformed into binding legal commitments. Soft law non-binding declarations, resolutions, and guidelines plays a pivotal role in norm-setting and influencing state behavior despite its lack of formal enforceability. Through a qualitative doctrinal approach, this study examines historical precedents, mechanisms of norm internalization, and case studies where soft law has contributed to the development of customary international law or informed treaty-making. The discussion focuses on instruments such as the Universal Declaration of Human Rights (UDHR), the UN Guiding Principles on Business and Human Rights, and the Yogyakarta Principles. The findings reveal that political pressure, judicial interpretation, and multilateral consensus are essential pathways in elevating soft law norms to hard law status. The paper concludes that while soft law cannot fully substitute binding treaties, its strategic use significantly contributes to the progressive development of international human rights law and may serve as a bridge toward universal and enforceable norms.